Evaluation of the relationship between color-tuning of photosynthetic excitons and thermodynamic stability of light-harvesting chromoproteins - Rätsep, M; Lehtmets, A; Kangur, L; Timpmann, K; Leiger, K; Wang-Otomo, Z-Y; Freiberg, A (Photosynthetica, 2023)
Color-tuning is a critical survival mechanism for photosynthetic organisms. Calcium ions are believed to enhance both spectral tuning and thermostability in obligatory calcium-containing sulfur purple bacteria. This study examined the thermo- and piezo stability of the LH1-RC complexes from two calcium-containing sulfur purple bacteria notable for their extreme red-shifted spectra. The results generally show limited reversibility of both temperature and pressure effects related to the malleability of calcium-binding sites. While the pressure-induced decomposition product closely resembles the calcium-depleted form of the chromoproteins, the thermally induced products reveal monomeric B777 and dimeric B820 forms of bacteriochlorophyll a, similar to those seen in non-sulfur purple bacteria treated with detergent. The study further found nearly unison melting of the protein tertiary and secondary structures. Overall, our findings do not support a direct link between color adjustment and thermodynamic stability in light-harvesting chromoproteins.
Keywords: circular dichroism; hydrostatic high pressure; LH1-RC complex; Ca-containing bacteria; purple bacteria